Helmet use in equestrian athletes: opportunities for intervention - Ansley Grimes Stanfill; Kayla Wynja; Xueyuan Cao; Drew Prescott; Sarah Shore; Brandon Baughman; Anthony Oddo; Jack W Tsao (Concussion, 2021)
Background: Equestrian athletes (horse riders) are at high risk for head injury, including concussions. Materials & methods: Adults riders were recruited via social media posting to complete a branching survey collecting data on demographics, riding experience, helmet use, injury history and concussion symptom knowledge. Results are reported as frequencies and percentages, with associations tested using chi-square with significance level p < 0.05. Results: Of the 2598 subjects, about 75% reported always wearing a helmet. Of those who did not, the most common reasons were that helmets are unnecessary (57.4%) or do not fit well (48.6%). Many indicated improper storage conditions and/or did not follow manufacturer’s replacement recommendations. Most (75.4%) reported a high level of comfort with recognizing concussion signs, with half experiencing a prior head injury. Conclusion: This information suggests opportunities for intervention to improve helmet use through increased fit, while the responses indicate a need for further education on proper helmet use.